2017
DOI: 10.1111/ases.12363
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a novel continuous incision technique for laparoscopic transcystic choledocholithotomy

Abstract: Introduction: The purpose of this study was to evaluate the safety and efficacy of a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the hospitals participating in our study, the proportion of LCBDE for treatment of CBDS patients was 1.8À19% for each hospital (data not shown). However, patients with multiple stones, duodenal diverticulum, severe strictures or obstructions, and severe kyphosis will require surgical methods [11,17,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In the hospitals participating in our study, the proportion of LCBDE for treatment of CBDS patients was 1.8À19% for each hospital (data not shown). However, patients with multiple stones, duodenal diverticulum, severe strictures or obstructions, and severe kyphosis will require surgical methods [11,17,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic choledocholithotomy with transcystic C-tube drainage results in an excellent rate of stone clearance, less bile leakage, less blood loss, acceptable mortality and morbidity rates, shortened hospital stay, and earlier social reintegration than conventional open surgery with transductal T-tube drainage[22,27,69,106-109]. However, in a laparoscopic approach, operative time was prolonged and cost becomes more expensive[110,111].…”
Section: Discussionmentioning
confidence: 99%
“…Operative time is greatly affected by the duration of stone removal[73,74]; detailed preoperative imaging studies shorten operative time[77]. Removal of impacted and/or large stones is especially difficult[27,73], although even an impacted stone will float after preoperative biliary drainage[76]. Preoperative evaluation with endoscopic retrograde cholangiography or cholangiography via drainage tube is strongly recommended[78].…”
Section: Preoperative Evaluation Of Bile Duct Stonesmentioning
confidence: 99%
“…[16] Some authors consider the transcystic approach as risky in stones of larger than 20 mm. [17] There is no unanimous opinion regarding the completion of choledochotomy with T-drainage, primary suture or stend, which is another issue of laparoscopic choledochotomy. We used T-drainage in all patients during our study, and T-drainage dislocation was observed in one patient, which was resolved by relaparoscopy.…”
Section: Discussionmentioning
confidence: 99%